2006
DOI: 10.1080/09513590600630470
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function abnormalities and antithyroid antibody prevalence in pregnant women at high risk for gestational diabetes mellitus

Abstract: Both gestational diabetes mellitus (GDM) and thyroid dysfunction in pregnancy compromise maternal and fetal health. The aim of the present study was to determine the prevalence of abnormal thyroid function and antithyroid antibodies during early pregnancy in a population at high risk for GDM. Serum free triiodothyronine (FT3), free thyroxine (FT4) and thyroid-stimulating hormone (TSH) were measured in 301 pregnant women who underwent routine 'universal screening' for GDM. The antithyroid peroxidase antibody (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 22 publications
1
47
0
2
Order By: Relevance
“…Feely et al documented that SCH coexisted in 30% cases of GDM 55 . Many other literatures have also documented an association of thyroid abnormalities, notably overt and subclinical hypothyroidism as well as autoimmune thyroiditis with GDM [56][57][58][59][60] . This correlation has been substantiated by depiction of an inverse association between Metforfin and TSH level 61,62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Feely et al documented that SCH coexisted in 30% cases of GDM 55 . Many other literatures have also documented an association of thyroid abnormalities, notably overt and subclinical hypothyroidism as well as autoimmune thyroiditis with GDM [56][57][58][59][60] . This correlation has been substantiated by depiction of an inverse association between Metforfin and TSH level 61,62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…They observed no statistically significant difference in free T 4 level between 2 group of gestational diabetes and healthy pregnant women. 18 Although, in a study, Velkoska et al indicated significant differences in free T 4 level in three groups of GDM, diabetes mellitus type I, and control group (11.7, 13.8, and 13.8 respectively) (p value <0.0001). In current study, women with gestational diabetes had normal TSH, but 10 % of them had free T 4 level below normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed contradict findings, which found no significant differentiate between GDM and non GDM groups regarding anti-TPO level. [17][18][19] In a study done by Agarwal et al, they observed that increased TSH level was associated with higher anti-TPO level (p value <0.001). 18 Velkoska et al reported prevalence of positive anti-TPO test in GDM, diabetes mellitus type I, and control group (15%, 30.8%, and 10% respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations